Sensitive bromatometric assay methods for finasteride in pharmaceuticals - Kanakapura, Basavaiah; Somashekar, Bankavadi Chikkaswamy; Anilkumar, Urdigere Rangachar; Ramakrishna, Veeraiah (Eclética Química, 2006)
Three sensitive spectrophotometric methods are presented for the determination of finas- teride in bulk and in tablets. The methods rely on the use of bromate-bromide reagent and three dyes namely, methyl orange, indigocarmine and thymol blue as reagents. They involve the addition of a measured excess of bromate-bromide reagent to finasteride in acid medium, and after the bromination reaction is judged to be complete, the unreacted bromine is determined by reacting with a fixed amount of either methylorange and measuring the absorbance at 520 nm (method A) or indigocarmine and measuring the absorbance at 610 nm (method B) or thymol blue and measuring the absorbance at 550 nm (method C). In all the methods, the amount of insitu generated bromine reacted corresponds to the amount of finasteride. The absorbance measured at the respective wavelength is found increase linear- ly with the concentration of finasteride. Beer’s law is obeyed in the ranges 0.25- 2.0, 0.5-6.0 and 1-12 μg mL -1 for method A, method B and method C, respectively.